Quantitative Assessment of Apodized Square Aperture - Mohammed, A. (Iraqi Journal of Science, 2025)
Two-dimensional computer simulations are carried out to quantify the quality ofapodized square aperture (ASA) in terms of the diffraction limited resolution and theefficiency of detection of faint companions. The study involve the quality of thepoint spread function (psf), and the modulation transfer function (MTF) of areference star. Annular apodized square aperture (AASA) is also considered in thisstudy. The results are then compared with the classical circular aperture.ASA shows high contrast which increases the possibility of detection of faintcompanions and AASA demonstrates significant high frequency components whichleads to high resolution.